Characterizing Geomorphology of Mesophotic Coral Reef Ecosystems in the Southwestern Gulf of Mexico: Implications for Conservation and Management - Mayorga-Martínez, Melissa; Bello-Pineda, Javier; Perales-Valdivia, Héctor; Pérez-España, Horacio; Heyman, William D. (Frontiers in Marine Science, 2021)
Coral reefs are the most biodiverse ecosystems on earth and are presently experiencing severe declines globally. Shallow coral reef ecosystems (<30 m) have been studied extensively while mesophotic coral ecosystems (MCE) are poorly studied. As a result, MCE are rarely included in marine reserve design and management, despite their ecological importance and connectivity to shallow reefs. In this study, we assessed the fine-scale topographic complexity, a proxy for structural complexity, for a group of coastal coral reefs in a marine park in the southwestern Gulf of Mexico, in depths between 2 and 49 m. We conducted hydrographic surveys using a semi-portable multibeam echosounder system to produce 3D bathymetry digital terrain models (DTM) with a 2.5 m spatial resolution for three submerged bank reefs and two emerging reefs. From these models, descriptive terrain parameters were calculated for each reef, including slope, aspect, curvature, rugosity and ruggedness. Results show that all reefs are predominantly northeast-southwest oriented, with well-defined leeward and windward sides. For the three submerged bank reefs, structural complexity increased with depth. Estimated mean ruggedness and rugosity were highest at 20–40 m depth range on windward side slopes. Emerging reefs showed high structural complexity, particularly at the 25–40 m depth range. We identified a spur and groove zone with maximum ruggedness (0.26) and rugosity (3.17) values, and four channels with steep slopes (68°) and dispersed mounds. We found that at mesophotic depths (>30 m), southern reefs basements from two distinct reefs merge to form a continuous complex. This has important management implications since presently, only 28.7% of this reef complex (mostly shallow areas) are within the existing limits of the marine park’s core zone. Considering the newly recognized importance of MCE, we propose expanding and reshaping the core zone to include the entire reef complex which mostly encompasses MCE with high structural complexity. Our study illustrates the value of semi-portable MBES for marine planning in developing countries and remote poorly studied areas.